Enhancing shear stability in laminated rock masses: A comparative study of traditional and resilient rock bolts - Chang Zhou; Chunni Han; Chunye Ying; Yaluo Mi; Qiang Wang; Tao Liu (Results in Engineering)
The movement of rock mass along the shear surface induces axial and normal shear forces in rock bolts, necessitating enhancements to their shear performance. A novel resilient rock bolt has been developed to accommodate large shear deformations by incorporating an adaptive section near the shear surface, based on plastic flow principles in gears and hinge connections. Multi-gears provide periodic resistance, enabling cyclical energy absorption and release. Two large physical model tests were conducted comparing ordinary and new resilient rock bolts, with vertical and horizontal soil pressures recorded. The results revealed that the new resilient rock bolt system operates through cycles of energy absorption, adaptation, and release. It exhibits smaller and more uniform stress compared to ordinary bolts and requires significantly larger shear displacement to fail, demonstrating superior co-deformation with the rock mass. Additionally, the new rock bolt minimizes prestress loss and more effectively transmits axial force to the stable rock layer. With a higher energy release coefficient (0.815) compared to others (<0.5), the new rock bolt substantially enhances the stability of the rock bolt system. This innovative design offers improved performance and reliability in rock mass stabilization.